(untitled) (Al-Farooq Journal of Sciences, 2026)
The financial sector is currently witnessing a significant transformation toward adopting sustainability concepts and responsible finance practices, driven by the growing global interest in environmental, social, and governance (ESG) issues, which have become essential determinants in evaluating institutional performance and their ability to create long-term value. This research aims to examine the application of Environmental, Social, and Governance (ESG) standards in Libyan financial institutions and companies by analyzing the concept of these standards, their dimensions, and their importance in enhancing the performance of financial and banking institutions. It also seeks to identify the main challenges hindering their implementation and propose appropriate mechanisms for their development within the Libyan context. The study adopts the descriptive analytical approach through reviewing and analyzing scientific literature and previous studies related to ESG standards, sustainable finance, and corporate governance, while focusing on the specific characteristics of the Libyan financial sector. The research findings indicate that the implementation of ESG standards has become a strategic necessity for financial institutions due to their role in improving risk management, enhancing transparency, supporting sustainable finance, and strengthening institutional competitiveness. The study also reveals that the application of ESG standards in Libyan financial institutions and companies remains at an early stage due to several challenges, including weak regulatory frameworks, limited non-financial disclosure practices, lack of reliable data, shortage of specialized expertise, and limited awareness of sustainable finance concepts. However, adopting these standards represents a significant opportunity for developing the Libyan financial sector by strengthening the role of financial institutions in supporting economic development and diversifying financing sources. The research recommends establishing a national framework for ESG implementation, enhancing the role of financial regulatory authorities, particularly the Central Bank of Libya, in promoting sustainable finance, developing non-financial disclosure systems, and building specialized human capacities to integrate sustainability principles into the strategies of Libyan financial institutions and companies.